Engineering of anp efficient mutant of Neisseria polysaccharea amylosucrase for the synthesis of controlled size maltooligosaccharides. (1st October 2017) - Vergès, Alizée; Barbe, Sophie; Cambon, Emmanuelle; Moulis, Claire; Tranier, Samuel; Remaud-Siméon, Magali; André, Isabelle
Highlights: Amylosucrase engineering led to an efficient mutant for oligosaccharide synthesis. Synthesis of controlled-size soluble maltooligosaccharides (2 < DP < 21). Abolished synthesis of insoluble glucan synthesis. Study of molecular and dynamic determinants involved in enzyme product specificity. Abstract: Amylosucrase from Neisseria polysaccharea naturally catalyzes the synthesis of α-1, 4 glucans from sucrose. The product profile is quite polydisperse, ranging from soluble chains called maltooligosaccharides to high-molecular weight insoluble amylose. This enzyme was recently subjected to engineering of its active site to enable recognition of non-natural acceptor substrates. Libraries of variants were constructed and screened on sucrose, allowing the identification of a mutant that showed a 6-fold enhanced activity toward sucrose compared to the wild-type enzyme. Furthermore, its product profile was unprecedented, as only soluble maltooligosaccharides of controlled size chains (2 < DP < 21) with a narrow polydispersity were observed. This variant, containing 9 mutations in the active site, was characterized at both biochemical and structural levels. Its x-ray structure was determined and further investigated by molecular dynamics to understand the molecular origins of its higher activity on sucrose and higher production of small maltooligosaccharides, with a totally abolished insoluble glucan synthesis.